The Role of Social Media in the ‘Syrian Uprising’ - Ahmad, Araz Ramazan; Hamasaeed, Nazakat Hussain Hamasaeed Hussain (Journal of Economic Development, Environment and People, 2015)
This paper, which is entitled ‘The Role of Social Media in the ‘Syrian Uprising’ aimed to report on survey research conducted which identify the role of played by social media in the ‘Syrian Uprising’ Currently social media tools were good mediums of electronic communication among protesters in Syria. Further, it was a vital medium for spreading information such as photos, videos and documents about the revolution for national, regional and international spheres. This paper looked at the impact and relationship between protesters and Syrian people who used social media ,technology and the nature of its role in the ‘Syrian Uprising ‘ as well as the study has made a controversial argument between different views of scholars about the subject and its case. This paper has interviewed 30 protesters inside Syria through a survey. This study, demonstrate the appeal that social media can have both positive and negative points in the ‘Syrian uprising’.